2022
DOI: 10.1007/s12672-022-00528-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrated in silico analysis of LRP2 mutations to immunotherapy efficacy in pan-cancer cohort

Abstract: Purpose Immunotherapy has emerged as a novel therapy, while many patients are refractory. Although, several biomarkers have been identified as predictive biomarkers for immunotherapy, such as tumor specific genes, PD-1/PD-L1, tumor mutation burn (TMB), and microsatellite instability (MSI), results remain unsatisfactory. The aim of this study is to evaluate the value of LRP2 mutations in predicating cancer immunotherapy. Methods We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…Multiple studies have shown that small structural differences in HSPG2 across diseases have antagonistic effects on tumor formation and metastasis; intact perlecan promotes the development of a vascular supply that supports tumor cell proliferation and the development of a variety of cancers, whereas bioactive perlecan fragments inhibit tumor development by targeting its vascular supply ( 22 , 23 ). LRP2 (rs2302694) mutations were detected in a range of cancers, with melanoma (28.18%), uterine sarcoma (17.99%), and lung squamous cell carcinoma (16.32%) with the highest mutation rates ( 24 ). A pan-cancer study found that LRP2 mutations were linked with increased immune cell infiltration, immune checkpoint gene expression, and significant enrichment of immune-related signaling pathways, as well as a better prognosis, compared to individuals who did not have LRP2 mutations ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that small structural differences in HSPG2 across diseases have antagonistic effects on tumor formation and metastasis; intact perlecan promotes the development of a vascular supply that supports tumor cell proliferation and the development of a variety of cancers, whereas bioactive perlecan fragments inhibit tumor development by targeting its vascular supply ( 22 , 23 ). LRP2 (rs2302694) mutations were detected in a range of cancers, with melanoma (28.18%), uterine sarcoma (17.99%), and lung squamous cell carcinoma (16.32%) with the highest mutation rates ( 24 ). A pan-cancer study found that LRP2 mutations were linked with increased immune cell infiltration, immune checkpoint gene expression, and significant enrichment of immune-related signaling pathways, as well as a better prognosis, compared to individuals who did not have LRP2 mutations ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…LRP2 (rs2302694) mutations were detected in a range of cancers, with melanoma (28.18%), uterine sarcoma (17.99%), and lung squamous cell carcinoma (16.32%) with the highest mutation rates ( 24 ). A pan-cancer study found that LRP2 mutations were linked with increased immune cell infiltration, immune checkpoint gene expression, and significant enrichment of immune-related signaling pathways, as well as a better prognosis, compared to individuals who did not have LRP2 mutations ( 24 ). Depletion of Lama5 (rs148927246, rs2274933) in lymph node stromal cells controls immunological responses to T cell migration and function, encourages branching angiogenesis, and modifies Notch signaling, which facilitates colorectal cancer spread to the liver ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“… 3 LRP2/megalin is expressed in a wide range of tissues, including the choroid plexus, the lung alveoli, the thyroid and parathyroid glands, and retina, in addition to proximal tubular cells within the kidney, and has been implicated in tumorigenesis in a range of human cancers, including colorectal cancer, melanoma, and lung cancer. 16 , 17 , 18 However, data remain limited in determining an association between malignancy and ABBA disease.…”
Section: Discussionmentioning
confidence: 99%
“…LRP2 is a coreceptor used to control acoustic hedgehog signaling in development and disease [ 38 ]. Mutations in LRP2 can be used as a biomarker for personalized tumor immunotherapy [ 39 ]. P2RY6, a receptor for nucleotide uridine 5′ -diphosphate, has been implicated in various human diseases, including obesity and autoimmune diseases [ 40 ].…”
Section: Discussionmentioning
confidence: 99%